2009
DOI: 10.1097/ftd.0b013e3181aa36cd
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Pharmacokinetics and Pharmacodynamics of the Calcineurin Inhibitors and Mycophenolic Acid: Possible Consequences for Therapeutic Drug Monitoring in Solid Organ Transplantation

Abstract: Although therapeutic drug monitoring (TDM) of immunosuppressive drugs has been an integral part of routine clinical practice in solid organ transplantation for many years, ongoing research in the field of immunosuppressive drug metabolism, pharmacokinetics, pharmacogenetics, pharmacodynamics, and clinical TDM keeps yielding new insights that might have future clinical implications. In this review, the authors will highlight some of these new insights for the calcineurin inhibitors (CNIs) cyclosporine and tacro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 238 publications
(370 reference statements)
4
109
0
2
Order By: Relevance
“…It was reported that patients carrying at least 1 CYP3A5*1 allele have a lower TAC concentration to dose ratio when compared with nonexpressors (CYP3A5*3/*3) in kidney, liver, lung, and heart transplant recipients [62]; it is obvious that individual pharmacogenetics could affect whole blood TAC concentrations and, consequently, increasing TAC concentrations may lead to an increase in drug-related adverse effects [63]. These preliminary results explained the interindividual variability of neurotoxicity at a genetic level and, furthermore, indicated that genetic polymorphisms might be useful to predict the susceptibility of a patient with an increased risk for TAC-related neurotoxicity rather than a pure concentration-based approach [64]. In this high-risk group for undesirable TAC complications, choosing a different immunosuppressive protocol or aiming at a lower threshold for stopping TAC might eventually allow to reduce the incidence of TAC-associated PRES and improve clinical outcome [64].…”
Section: Managementmentioning
confidence: 96%
“…It was reported that patients carrying at least 1 CYP3A5*1 allele have a lower TAC concentration to dose ratio when compared with nonexpressors (CYP3A5*3/*3) in kidney, liver, lung, and heart transplant recipients [62]; it is obvious that individual pharmacogenetics could affect whole blood TAC concentrations and, consequently, increasing TAC concentrations may lead to an increase in drug-related adverse effects [63]. These preliminary results explained the interindividual variability of neurotoxicity at a genetic level and, furthermore, indicated that genetic polymorphisms might be useful to predict the susceptibility of a patient with an increased risk for TAC-related neurotoxicity rather than a pure concentration-based approach [64]. In this high-risk group for undesirable TAC complications, choosing a different immunosuppressive protocol or aiming at a lower threshold for stopping TAC might eventually allow to reduce the incidence of TAC-associated PRES and improve clinical outcome [64].…”
Section: Managementmentioning
confidence: 96%
“…Due to a narrow therapeutic index and its large interpatient and intrapatient pharmacokinetic variability, therapeutic drug monitoring (TDM) is routinely performed for individualization of the Tac dose to maintain drug efficacy and minimize the consequences of overexposure [18]. As allografts are nowadays rarely lost as a consequence of acute rejection, adverse events associated with long-term immunosuppression have become increasingly evident [19].…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Preliminary data suggest that in the early posttransplantation period, CsA intracellular concentrations or AUC 0 -12h in peripheral blood mononuclear cells (PBMC) would be lower in patients experiencing acute rejection or would decrease during the week preceding the acute rejection episode, and that TAC concentrations in PBMC would exhibit a very high interindividual variability (7 ). However, at the present time, the extemporaneous isolation of PBMC from whole blood is laborious.…”
mentioning
confidence: 99%
“…However, the determination of tissue CNI concentrations is unlikely to make its way into clinical practice (7 ).…”
mentioning
confidence: 99%